2020
DOI: 10.1177/0269215520983486
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of prefabricated and custom made resting hand splints for individuals with cervical spinal cord injury: A randomized controlled trial

Abstract: Objective: To compare prefabricated and custom resting hand splints and establish the feasibility of splinting research for larger scale trials. Design: A Randomized controlled pilot study where the randomization unit was each hand, rather than each individual. Setting: Thirty-two-bed spinal cord injury and multi-trauma rehabilitation unit in an urban academic rehabilitation center. Subjects: Thirty-six hands from 19 individuals with cervical spinal cord injury were enrolled during their acute rehabilitation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Using orthoses can improve the patient's hand function, which is helpful for ADL, such as eating. A study comparing prefabricated and custommade resting hand splints among SCI patients showed no statistical difference (37). Although custom-made orthotic devices are generally recommended in clinical practice, sometimes their advantages are minimal, and they have the disadvantages of being timeconsuming and expensive.…”
Section: Wrist and Hand Orthotic Devicesmentioning
confidence: 99%
“…Using orthoses can improve the patient's hand function, which is helpful for ADL, such as eating. A study comparing prefabricated and custommade resting hand splints among SCI patients showed no statistical difference (37). Although custom-made orthotic devices are generally recommended in clinical practice, sometimes their advantages are minimal, and they have the disadvantages of being timeconsuming and expensive.…”
Section: Wrist and Hand Orthotic Devicesmentioning
confidence: 99%
“…The finger splints can be broadly categorized as prefabricated or customized [10]. Evidence of better performance of the customized splints, when compared with prefabricated ones, is found in the literature [11,12]. Both these types of splints can be fabricated using different types of materials available such as plaster, fiberglass, metal, foam, thermoplastics, carbon fiber, and other materials [13,14].…”
Section: Introductionmentioning
confidence: 99%